Status Hemodinamik Pasien Intradialisis - Selvia, Inka; Deli, Hellena; Hasanah, Oswati (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
51 Hemodialysis is one of the therapies for CRF sufferers to replace damaged kidney function. During the hemodialysis process, patients experience intradialytic complications such as hemodynamic disorders. This study aims to determine the hemodynamic status of intradialytic patients. This study used a descriptive design. This study used a purposive sampling technique (n= 63) that used univariate analysis. Results blood pressure majority of the respondent at 1st and 2nd hours had isolated systolic hypertension (39.7% and 42.9%) and hypotension (1.6%), at the third hour had hypertension (49.3%), at the fourth hour the majority of respondents had normal blood pressure (38.1%). The majority of heart rate intradialytic of respondents had normal, tachycardia was found in the third and fourth hours (6.3% and 3.2%). The majority of Intradialysis respiratory rate of respondents had normal, tachypnea was found during intradialytic who the most respondents were at the third hour (19.0%). The majority of temperature intradialytic of respondents had normal, hyperthermia was found in the second and third hours (1.6% and 3.2%). Conclusion: the hemodynamic status of patients at Arifin Achmad Hospital Riau Province in intradialytic had changed and must be monitored every hour intradialytic, especially in the third hour.